2013
DOI: 10.19052/mv.2633
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiología de la leptospirosis en bovinos con trastornos reproductivos en el municipio de Montería, Colombia

Abstract: Se realizó un estudio descriptivo para determinar la prevalencia de leptospirosis en bovinos con trastornos reproductivos de zonas rurales de Montería, Colombia. Se colectaron muestras de suero de 26 toros y 137 vacas procedentes de 28 fincas con antecedentes de problemas reproductivos, los cuales fueron analizados mediante técnica de microaglutinación (MAT) para detección de anticuerpos contra Leptospira. Se utilizaron antígenos de los serovares pomona, hardjo, canicola, grippotyphosa e icterohaemorrhagiae. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…No significant statistical association was obtained between PI3, leptospirosis, and neosporosis with the breed and age group of the cattle evaluated. This agrees with the findings of Fernandez et al [ 29 ], Betancur et al [ 32 ], Cruz-Estupiñan et al [ 26 ], and Ansari-lari [ 7 ] but differs with Bedoya et al [ 25 ], who found an association with age and established it as a risk factor for infection with Neospora . Doria-Ramos et al [ 30 ] reported a relationship between the breed and age with the presentation of PI3; however, in Chiquinquirá, no association was found between seropositivity for antibodies against PI3 and the described variables.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…No significant statistical association was obtained between PI3, leptospirosis, and neosporosis with the breed and age group of the cattle evaluated. This agrees with the findings of Fernandez et al [ 29 ], Betancur et al [ 32 ], Cruz-Estupiñan et al [ 26 ], and Ansari-lari [ 7 ] but differs with Bedoya et al [ 25 ], who found an association with age and established it as a risk factor for infection with Neospora . Doria-Ramos et al [ 30 ] reported a relationship between the breed and age with the presentation of PI3; however, in Chiquinquirá, no association was found between seropositivity for antibodies against PI3 and the described variables.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding PI3, neosporosis, and leptospirosis, cattle aged 1–4 years presented the highest seropositivity, which is not in agreement with the studies by Betancur et al [ 27 ], Betancur et al [ 32 ], Cardona et al, and Bedoya et al [ 22 , 25 ], who found the highest seroprevalences for PI3, leptospirosis, and neosporosis, respectively, in older cattle, and this may occur because infected cattle remain infected for life; this effect is likely to represent the risk of cumulative exposure to the agent in the environment as the animals' age [ 37 , 38 ].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Studies were conducted involving beef cattle and dairy cattle. Low fertility, pregnancy losses and a reduction in milk production were reported [ 60 ]. The most frequent serovars predicted by the MAT were Hardjo, Wolfii and Tarassovi [ 57 , 61 , 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%